Signal Processing for Wireless Communication Systems - Poor, H. Vincent (Kluwer)
Reimpresión de una edición especial de la revista Journal of VLSI Signal Processing Systems for Signal, Image, and Video Technology que corresponde al volumen 30, números 1-3 de enero de 2002.